Contour generation for multivalued streamed images using crack codes on a GPU - Butt, M. Usman; Morris, John; Patel, Nitish; Biglari-Abhari, Morteza (Food Agricultural Sciences and Technology, 2015)
We describe an effi cient GPU algorithm which extracts multiple contours from an image. The algorithm uses crack codes to generate contours which sit logically between adjacent image values; it works scan line by scan line and it can generate multiple contours in parallel with an image streamed directly from a camera. Whilst specifi cally targeted at detecting object contours in stereo disparity maps, it can also be used for general segmentation with a trivial change to the code generating the crack code masks. Using a 480 ALU 1.4 GHz nVidia GPU, it can generate 25000 contours from a real 2048 × 768 resolution 128 level disparity map image in 29 ms if the contours are further processed in the GPU or 39 ms if contours are transferred to the host - typically 40 times faster than an OpenCV CPU implementation.